The Influence Of The Website's Atmosphere On Online Consumer Behavior And Its Relationship To Flow: Case Study Of Online Travel In Indonesia - Nanang F Kurniawan; Eko Madiasto; Primidya KM Soesilo (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
In this decade, studies of website atmospherics and flow experiences have received much attention from researchers and are very broad. At present, there are still few fields of study that study the relationship between the atmosphere website and a flow experience. In this study aims to examine the factors that have an impact on website atmospherics and flow experiences that can affect consumer behavior (Enjoyment shopping, Intimacy, and Intention) in the use of online travel services websites in Indonesia. In the development of this study, using the stimulus-organism-response (S-O-R) framework as a theoretical basis, the findings of this study are expected to show that the design atmosphere in websites has a positive impact on improving the enjoyment shopping, Intimacy and Intention of purchases for online travel agents in Indonesia.